Implementasi Berbasis Evidence Terapi Handheld Fan untuk Pola Napas Tidak Efektif pada Pasien CHF - Laidy Novie Rahmawati; Erna Rochmawati; Nita Sritunjung (Jurnal Ilmu Kesehatan dan Gizi, 2026)
Congestive heart failure (CHF) is a cardiovascular disease that frequently causes shortness of breath (dyspnea) and negatively impacts patients’ quality of life. The management of dyspnea involves not only pharmacological approaches but also nonpharmacological interventions, one of which is handheld fan therapy, which works by stimulating sensory receptors in the facial area. This study aims to describe the effect of handheld fan therapy on reducing shortness of breath in patients with CHF. This study employed a descriptive design using a case report method on a single 63-year-old female patient diagnosed with CHF. The intervention was conducted over four days, involving the use of a handheld fan for 10 minutes, held at a distance of 15–30 cm from the face and directed toward the nose and mouth. Measurements were taken before and after the intervention using respiratory rate and oxygen saturation as parameters. The results showed a gradual decrease in respiratory rate from 24 breaths/minute to 18 breaths/minute, as well as an increase in oxygen saturation from 91% to 96% during the intervention period. These findings indicate an improvement in breathing patterns and increased respiratory efficiency in the patient. Handheld fan therapy is effective as a nonpharmacological intervention for reducing shortness of breath and improving oxygenation in patients with CHF. This intervention is safe, easy to use, and can be implemented as a complementary therapy in nursing practice.